HUBUNGAN PENGETAHUAN IMS DENGAN KEPUTUSAN WANITA MENJADI PEKERJA SEKSUAL DI KECAMATAN BANJARSARI - Syefira Ayu Johar (Program Studi Perekam Medis & Informasi Kesehatan, 2019)
In Indonesia, the number of cases of people with HIV from 2005 to 2017 as many as 280,623, and the case of AIDS as much as 102,667. The dominant HIV infection occurred in heterosexual by 69.6%. In Central Java, the number of new HIV cases in 2017 was 5,425, while the number of new cases of AIDS was 1,719. While the city of Surakarta has the second highest HIV case in Central Java after Semarang district of 38 HIV cases and 46 AIDS cases in September 2017. The study used observational analytical studies, with case control ¬ approach and Chi-square analysis. The subject is a sexual worker woman with a case and a control group (not a sexual worker) in the district of Banjarsari, Surakarta with the number of subjects of each group of 100 people. The dependent variable is a woman's decision to be a sexual worker and an independent variable is IMS knowledge. A woman's decision to become a sexual worker is related and statistically significant to IMS knowledge (OR = 0.08; CI 95% = 0.04 to 0.16; p < < 0.001). Women's decisions become sexual workers in relation to IMS knowledge.